Excellent heat transfer and phase transformation performance of erythritol/graphene composite phase change materials - Yan, Xiaoxin; Zhao, Haibo; Feng, Yanhui; Qiu, Lin; Lin, Lin; Zhang, Xinxin; Ohara, Taku (Composites. Part B, Engineering, 2022)
As a phase change material, erythritol has two main disadvantages: low thermal conductivity and high supercooling degree. In this study, we proposed a novel erythritol/graphene composite phase change material, and its thermal properties were predicted by molecular dynamics simulation. The effects of the graphene mass fraction, size and number of layers on the thermal conductivity and phase transition characteristics, including the melting point and supercooling degree, were analyzed. The mechanism behind the above phenomena was revealed from a micro perspective. The results show that graphene can not only improve the thermal conductivity of the composites but also reduce the supercooling degree, thus improving the thermal properties of erythritol. The thermal conductivity of the composites increases with increasing graphene amount, size and number of layers. When the mass fraction of graphene increased to 8 wt%, the thermal conductivity doubled. The melting point of erythritol can be effectively controlled by changing the amount, size and number of layers of graphene. This study can provide guidance for the design and application of erythritol-based composite phase change materials. [Display omitted] •Thermal properties of erythritol/graphene composite were calculated by MD method.•Thermal conductivity of the composite can reach twice of that of pure erythritol.•Graphene can significantly suppress the supercooling degree from 68 °C to 21 °C.•The microscopic mechanism of thermal performance improvement was revealed.